Imagery vividness ratings during exposure treatment for posttraumatic stress disorder as a predictor of treatment outcome. (June 2015) - Mota, Natalie P.; Schaumberg, Katherine; Vinci, Christine; Sippel, Lauren M.; Jackson, Michelle; Schumacher, Julie A.; Coffey, Scott F.
Abstract: Within exposure-based trauma treatments for posttraumatic stress disorder (PTSD), imagery vividness during imaginal exposure of the traumatic memory is an understudied but potentially important predictor of treatment outcome. Further, to our knowledge, this relationship has only been studied in women to date, and never among individuals with PTSD and substance use disorders which could impact ability to produce vivid mental imagery and its impact. The current study investigated whether imagery vividness ratings during in-session exposure predicted post-treatment PTSD symptom severity in a sample of men and women with comorbid PTSD and substance use disorders, and also examined whether gender moderated this relationship. A sample of 71 participants who received an exposure-based trauma treatment were included in the analyses. PTSD symptom severity was assessed using both the Clinician Administered PTSD Scale (CAPS) and the Impact of Event Scale-Revised (IES-R). Results varied according to method of assessing PTSD symptom severity. Higher imagery vividness was associated with better treatment outcome when assessed by the CAPS, with vividness in later sessions relating more strongly to outcome than vividness in earlier sessions. With the IES-R, higher imagery vividness ratings predicted more favorable treatment outcome for men, but less favorable treatment outcomes for women. Findings are discussed in the context of using imagery vividness to maximize treatment outcomes and future research directions involving scientific replication. Highlights: Imagery vividness was lower in men than in women and maintained greater stability over treatment in men. Imagery vividness was a weaker predictor of SUDS as treatment progressed. Imagery vividness was negatively related to CAPS scores post-treatment, particularly in later sessions. Imagery vividness was related to fewer symptoms on the IES-R for men and higher symptoms for women.